2011
DOI: 10.1111/j.1538-7836.2011.04243.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of von Willebrand factor levels and activity in relation to the risk of cardiovascular disease: a review

Abstract: To cite this article: van Schie MC, van Loon JE, de Maat MPM, Leebeek FWG. Genetic determinants of von Willebrand factor levels and activity in relation to the risk of cardiovascular disease. A review. J Thromb Haemost 2011; 9: 899-908.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 94 publications
(132 reference statements)
3
48
0
1
Order By: Relevance
“…It has been well established that common genetic polymorphisms in the VWF gene contribute to the variability in VWF:Ag levels. [35][36][37] The most significant SNP that marked the VWF locus was rs216303:T4C, which is located within an intronic region. Until recently, intronic polymorphisms were often considered less relevant for disease development and regulating protein levels in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that common genetic polymorphisms in the VWF gene contribute to the variability in VWF:Ag levels. [35][36][37] The most significant SNP that marked the VWF locus was rs216303:T4C, which is located within an intronic region. Until recently, intronic polymorphisms were often considered less relevant for disease development and regulating protein levels in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive thrombus formation after plaque rupture remains difficult to predict and can be linked to hyperactive platelet function. 1,2 Therefore, low-dose aspirin to inhibit platelet cyclooxygenase-1 (COX-1) and clopidogrel to inhibit platelet P2Y 12 signaling are used widely in patients with cardiovascular risks, although patient response to these drugs can vary.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Similarly, platelet dysfunction or antiplatelet therapy can be associated with bleeding risks. [5][6][7] Furthermore, the function of blood is highly dependent on hemodynamic forces; examples include shear-induced platelet activation at Ͼ 5000/s shear rate, 8,9 requirement of VWF in arterial thrombosis, [10][11][12] shear effects on VWF structure/function and GPIb-VWF A1 domain-bonding dynamics, [13][14][15][16][17] RBC-dependent platelet migration toward the wall, 18,19 and convection-enhanced mass transfer to and from local zones of clotting or bleeding. 20,21 Defining, quantifying, and linking a patient's unique platelet phenotype or coagulation phenotype under hemodynamic conditions to clinical risk remains a diagnostic challenge.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Non-O blood types are associated with higher levels of vWF and FVIII, procoagulant proteins that circulate as a complex in blood, 11,12 because the ABO antigen affects clearance of vWF. 15 Levels of both vWF and FVIII are associated with thrombosis, 16 and were recently linked to dementia risk. 17 A recent report demonstrating an association between blood type AB and stroke risk found that 60% of that association was mediated by differences in FVIII level.…”
mentioning
confidence: 99%